CD8 agonism functionally activates memory T cells and enhances antitumor immunity. Issue 5 (21st May 2022) - Madi, Alaa; Weisshaar, Nina; Buettner, Michael; Poschet, Gernot; Ma, Sicong; Wu, Jingxia; Mieg, Alessa; Hering, Marvin; Ming, Yanan; Mohr, Kerstin; ten Bosch, Nora; Cui, Guoliang
Abstract: Memory CD8 + T cells mature after antigen clearance and ultimately express CD8 protein at levels higher than those detected in effector CD8 + T cells. However, it is not clear whether engagement of CD8 in the absence of antigenic stimulation will result in the functional activation of T cells. Here, we found that CD8 antibody‐mediated activation of memory CD8 + T cells triggered T cell receptor (TCR) downstream signaling, enhanced T cell‐mediated cytotoxicity and promoted effector cytokine production in a glucose‐ and glutamine‐dependent manner. Furthermore, pretreatment of memory CD8 + T cells with an agonistic anti‐CD8 antibody enhanced their tumoricidal activity in vitro and in vivo. From these studies, we conclude that CD8 agonism activates glucose and glutamine metabolism in memory T cells and enhances the efficacy of memory T cell‐based cancer immunotherapy. Abstract : What's new? Memory CD8 + T cells mature after antigen clearance and ultimately express high levels of CD8 protein. However, it is unclear whether engagement of CD8 in the absence of antigenic stimulation could result in the functional activation of T cells. Our study shows that CD8 agonists can activate memory T‐cell glucose and glutamine metabolism in the absence of T‐cell receptor stimulation. Furthermore, CD8 agonists can enhance the efficacy of memory T cell‐based cancer immunotherapy. The authors propose targeting CD8 as a potentially useful, intrinsically specific and importantly, tumor‐agnostic approach to antitumor immunotherapy.